Does innovation matter for firm’s financial inclusion? Evidence from Enterprise Surveys in Cameroon (International Journal of Scientific Research and Management (IJSRM), 2022)
This study aims at evaluating the impacts of innovation on financial inclusion in Cameroon. This specifically involves evaluating the effects of innovation on access, availability, use and the composite index of financial inclusion of companies in Cameroon. To achieve these goals, we used data from the World Bank (Enterprise Survey) from a survey of 361 manufacturing and service companies in 2016. Using the probit model, several results were obtained. (i) The more the company’s new products or services are new to its main market, and the more it invests in Research & Development activities, the more access it has to financial services; (ii) the more the company invests in Research & Development, the more it has overdraft or overdraft facilities; (iii) the more a company invests in Research & Development, the more it is financially included. Thus, we can recommend to Cameroonian companies to invest more in Research & Development in order to benefit from financial services from financial institutions.